Deposition of Ta2O5 Film on Commercial Pure Titanium Disk by Modified Reactive Plasma Sputtering Technique (Medico Legal Update, 2020)
Background: Now days the interest of implantology is to improve Osseo integration by find materials which accelerate bone formation at bone implant interface to provide immediate or early loading after placement of dental implant and eliminate waiting period which is un favorite and disturbs patients. Titanium is most common material for dental implant, but still need some modification for surface properties chemically and physically by using an other material such as tantalum which is gaining more attention as a new metallic biomaterial. Coating the surface of implant is an important way for development of surface properties of titanium. plasma Ta2O5 used for surface modification, which has several advantages such as increasing surface roughness, changing surface topography and increasing the wettability of the surface.Aim of study: To evaluate the action of Ta2O5 coating by modified plasma sputtering technique of commercially pure titanium disk on surface roughness, wettability and surface chemical composition in comparison to non-coated surface.Materials and methods: All tested group were two groups in this study which include un -coated commercial pure titanium disks and Ta2O5 coated commercial pure titanium. Modified reactive plasma sputtering technique was used to coat CpTi with Ta2O5 at 4,6,8, hr. Analysis of surface characterization by x-ray diffraction (XRD) analysis, scanning electron microscope (SEM), energy dispersive spectroscopy(EDS) were carried out on the coated surfaces of the disks, contact angle measurement was achieved by applying drop of saline on the surface of coated disks and compared to non- coated one.Results: The result of Ta2O5 coated specimen at times (4,6,8) showed that 8 hr. coating time was the best time. X-ray diffraction analysis show new peak formation for CpTi coated witht Ta2O5 disk which was not present in non- coated CpTi disk. The results showed that the rough surface was more and better distribution in CpTi coated with Ta2O5 disk than non- coated CpTi disk which improve by electron scanning microscope, wettability of Ta2O5 coated disk was more than wettability of non- coated CpTi disk.